Application of multiple-criteria decision-making techniques and approaches to evaluating of service quality: a systematic review of the literature - Mardani, Abbas; Jusoh, Ahmad; Zavadskas, Edmundas Kazimieras; Khalifah, Zainab; Md Nor, Khalil (Journal of Business Economics and Management, 2015)
The main purpose of this paper is to present a systematic review of multiple- criteria decision-making (MCDM) techniques used in the assessment of service qual- ity. This study reviewed a total of 79 articles from 51 journals, published from 2001 to 2015. Articles were classified into 10 application areas and scopes. Furthermore, articles were categorised based on an author, year, application area, the nationality of the author, ‏technique, a number of criteria, research purpose, gap and research problem, results and outcome. The best criteria were determined in each article. The results of this study re- vealed that more papers on MCDM were published in 2011 than in any other year. Inte- grated techniques, analytic hierarchy process (AHP) and fuzzy AHP methods, were ranked as first and second methods in use, respectively. Finally, the airline industry was ranked as the first application area, in which previous studies applied MCDM techniques for the evaluation of the service quality. This research contributes to the existing literature on the service quality and MCDM. The research outputs are valuable to academics scholars and leaders of organisations and industries in the field of service quality evaluation.